2019
DOI: 10.1021/acs.jpclett.9b01023
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Capture of CO2 through Entropic Effect Induced by Reversible Trans–Cis Isomerization of Light-Responsive Ionic Liquids

Abstract: Despite a great deal of gas capture strategies based on ionic liquids, reversible tuning of gas absorption by pure ionic liquids using light irradiation has never been reported. Herein, we demonstrate a novel strategy for tuning the capture of CO 2 by light-responsive ionic liquids through reversible trans−cis isomerization. These light-responsive ionic liquids were constructed by tailoring the azobenzene group to the cationic moiety, which exhibited different CO 2 absorption ability before and after ultraviol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…As mentioned above, serious intermolecular interactions inhibit structural isomerization because of the significant restriction in molecular motion, and therefore many research groups have investigated the photoisomerization behavior of azo group-containing ILs dissolved in organic solvents or an ordinary IL . Photoisomerization of stilbene-containing ILs has also been investigated in acetonitrile solution, , although the back-reaction from the nonfluorescent liquid cis form to the fluorescent solid trans form can be initiated by UV irradiation, as mentioned above.…”
Section: Photochromismmentioning
confidence: 99%
“…As mentioned above, serious intermolecular interactions inhibit structural isomerization because of the significant restriction in molecular motion, and therefore many research groups have investigated the photoisomerization behavior of azo group-containing ILs dissolved in organic solvents or an ordinary IL . Photoisomerization of stilbene-containing ILs has also been investigated in acetonitrile solution, , although the back-reaction from the nonfluorescent liquid cis form to the fluorescent solid trans form can be initiated by UV irradiation, as mentioned above.…”
Section: Photochromismmentioning
confidence: 99%
“…The sharp increase in CO 2 emissions is an urgent issue involved in global warming. Thus, efficient CO 2 capture has been a subject of particular interest in recent years. , The adsorption of CO 2 by porous materials has emerged as a promising method for eliminating atmospheric CO 2 . Understanding the mechanisms of CO 2 adsorption in porous materials thus plays a crucial role in CO 2 capture. An adsorption site, i.e., a specific position in an adsorbent for an adsorbate, is a fundamental concept in adsorption mechanisms. A considerable number of studies have demonstrated the heterogeneity of adsorption sites in some porous adsorbents, and this heterogeneity significantly affects adsorption properties, especially the adsorption heat. …”
Section: Introductionmentioning
confidence: 99%
“…In response to the external environment, the structures and properties of stimuli‐responsive ILs are changed and lead to the regulation of aggregation structure and phase behavior, which lay the foundation for the use of such ILs. Due to their special on‐off properties and unique controllable and reversible characteristics, the stimuli‐responsive ILs successfully meet the needs of homogeneous reaction, heterogeneous separation, ILs recovery, and system circulation in applications, such as catalysis, extraction, separation, [ 93‐94,108,112,144‐146 ] 3D netlike porous films, [ 46 ] CO 2 absorption, [ 149 ] etc . Moreover, the use of simulation methods such as CO 2 , magnetism, temperature, and light is more attractive in practical applications as additional substances can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…reported the ILs composed quaternary phosphine cation containing azophenyl group and 1,2,4‐triazolium anion exhibited different absorption capacities for CO 2 before and after UV irradiation, as shown in Figure 27. [ 149 ] At 20 °C and 1 bar, the capacity of azoIL b to absorb CO 2 dropped sharply from the original 0.92 mol·mol –1 to 0.63 mol·mol –1 after UV light irradiation. After heating to 80 °C with N 2 purging or Vis light irradiation, the cis ‐ azoIL b ‐CO 2 complex returned to trans ‐ azoIL b ‐CO 2 state with the reduction of CO 2 capacity to 0.89 mol·mol –1 .…”
Section: Applications Of Stimuli‐responsive Ilsmentioning
confidence: 99%